Selecting the location of distribution centre in logistics operations : a conceptual framework and case study - Thai, Vinh Van (2012)
This paper presents the outcomes of a study of the choice of location for distribution centres in logistics operations. A conceptual framework of location selection for distribution centre is worked out through three main stages. At the first stage, a general geographical area for distribution centre is identified based on the Centre of Gravity principle, taking into consideration socio-economic factors. The second stage of the selection process involves the identification of alternative locations for the distribution centre and the airports and seaports to be used for inbound and outbound cargo flows within the defined general geographical area. The third stage focuses on specific site selection among the identified alternative locations for the distribution centre based on the quantitative approach. This involves a mathematical model which aims to optimise either the total distribution cost or the integration of total distance transport with given relevant volumes of cargo. In order to illustrate the conceptual framework, a case study of a logistics service provider will be provided. Data from the case study proved that the conceptual framework for selection is valid and can be of value to logistics companies in their operations and management.